2015
DOI: 10.1002/jmv.24400
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of Crimean–Congo hemorrhagic fever in Bulgaria—An update

Abstract: Crimean-Congo hemorrhagic fever (CCHF) is endemic in Bulgaria. During 2013-2014, 11 confirmed CCHF cases have been reported in the country (seven in 2013 and four in 2014). The present study provides the CCHF molecular epidemiology in Bulgaria based on all currently available S, M, and L RNA segment nucleotide sequences spanning the years 1978-2014. A relatively low genetic difference (0-6%, the maximum seen in the M RNA segment) was seen among the CCHFV sequences suggesting that a slow evolving CCHFV strain b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
(35 reference statements)
0
9
0
1
Order By: Relevance
“…Data from the Bulgarian Ministry of Health suggest a fourfold reduction in reported CCHF cases over a 22 year time period (1953–1974: 1105 cases; 1975–1996, 279 cases) [61]. Unfortunately, however, this was the extent of the efficacy studies at the time and while there has been a reduction in cases, data indicates that this may not necessarily be the result of the vaccine but due to a multitude of factors which have decreased tick exposure in the region per se [62]. In addition, there is a lack of data regarding the incidence of CCHF in the same time frame in neighbouring countries, which also brings into question the analysis of vaccine efficacy at the time [63].…”
Section: The Case and Need For Vaccinesmentioning
confidence: 99%
“…Data from the Bulgarian Ministry of Health suggest a fourfold reduction in reported CCHF cases over a 22 year time period (1953–1974: 1105 cases; 1975–1996, 279 cases) [61]. Unfortunately, however, this was the extent of the efficacy studies at the time and while there has been a reduction in cases, data indicates that this may not necessarily be the result of the vaccine but due to a multitude of factors which have decreased tick exposure in the region per se [62]. In addition, there is a lack of data regarding the incidence of CCHF in the same time frame in neighbouring countries, which also brings into question the analysis of vaccine efficacy at the time [63].…”
Section: The Case and Need For Vaccinesmentioning
confidence: 99%
“…Since 1974 it has been used to immunize mainly military and medical personnel, farmers, and persons living or working in regions of endemicity. A 4-fold reduction in the number of reported Crimean-Congo hemorrhagic fever cases in Bulgaria has been observed over a 21-year period following initiation of vaccination (8, 9). A recent study found that this vaccine elicited both a cellular and humoral response to CCHFV (9), but neutralizing antibody titers were low, even in individuals that who had received four doses (3, 7).…”
Section: Introductionmentioning
confidence: 99%
“…A 4-fold reduction in the number of reported Crimean-Congo hemorrhagic fever cases in Bulgaria has been observed over a 21-year period following initiation of vaccination (8, 9). A recent study found that this vaccine elicited both a cellular and humoral response to CCHFV (9), but neutralizing antibody titers were low, even in individuals that who had received four doses (3, 7). Controlled studies on protective efficacy have not been reported with this vaccine, and, due to its crude preparation, it is unlikely to gain widespread international regulatory approval.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of hsa‐miR‐451 also increases PBMCs infected with Dengue virus serotype 2, with a concomitant elevation of proinflammatory cytokines such as CCL5, IL‐6, and IL‐8 [Qi et al, ]. These findings correlate with the cytokine profiles observed in individuals with CCHF [Papa et al, , ], as well as in Hantavirus‐induced hemorrhagic fever with renal syndrome (HFRS) [Kyriakidis and Papa, ]. A similar cytokine imbalance is associated with disease progression and occurs during viral hemorrhagic fevers, regardless of the etiologic agent.…”
Section: Discussionmentioning
confidence: 97%